An evaluation of the impact of SG1 disproportionation and the addition of styrene in NMP of methyl methacrylate. Issue 7 (12th February 2018) - Fierens, Stijn K.; Van Steenberge, Paul H. M.; Vermeire, Florence; Reyniers, Marie‐Françoise; Marin, Guy B.; D'hooge, Dagmar R.
Abstract : A kinetic modeling study is presented for batch nitroxide mediated polymerization (NMP) of methyl methacrylate (MMA; nitroxide: N‐tert‐butyl‐N‐[1‐diethylphosphono‐(2, 2‐dimethylpropyl)] (SG1)). Arrhenius parameters for SG1 disproportionation (A = 1.4 10 7 L mol −1 s −1 ; Ea = 23 kJ mol −1 ) are reported, based on homopolymerization data accounting for unavoidable temperature variations with increasing time, that is, nonisothermicity. For low targeted chain lengths (TCLs ≤ 300), this nonisothermicity is also relevant for NMP of MMA with a small amount of styrene. Parameter tuning to copolymerization data confirms a penultimate monomer unit effect for activation (sa2 = ka12 /ka22 =6.7; 363 K; 1: MMA; 2: styrene). To obtain, for a broad TCL range (up to 800), a dispersity well below 1.3 an initial styrene mass fraction of ca. 10% is required. An interpretation of the comonomer incorporation is performed by calculating the fractions of activation‐growth‐deactivation cycles with a given amount of monomer units and the copolymer composition distribution . © 2018 American Institute of Chemical Engineers AIChE J, 64: 2545–2559, 2018